Microelements in Human Fertility: A Comprehensive Literature Review (2015–2025) - Kaźmierczak, Joanna; Jurczak, Anna; Kiełbasa, Paweł; Komala, Weronika; Rabcewicz, Cyryl; Kowalska, Marta; Dworak, Michał; Kotucha, Kornela; Kapłon, Katarzyna; Góra, Jacek (Journal of Education, Health and Sport, 2025)
Introduction and purpose Microelements are essential nutrients required in small amounts but have profound physiological and biochemical roles in human reproduction. The main purpose of this review is to present the current state of knowledge regarding the effects of zinc, selenium, iodine, copper, iron, manganese, and magnesium on male and female fertility. The analysis highlights how deficiencies, excesses, and synergistic interactions among these elements affect gametogenesis, hormonal balance, oxidative stress, epigenetic modifications, and pregnancy outcomes. Through a synthesis of clinical, biochemical, and epidemiological findings, this paper emphasizes the need for micronutrient optimization as an adjunct strategy in managing infertility. Material and methods This review follows a comprehensive narrative synthesis approach to evaluate the role of microelements in human fertility, with a focus on zinc, selenium, iodine, copper, iron, manganese, and magnesium. A review was based on the analysis of 44 peer-reviewed articles, clinical, biochemical, and epidemiological studies published between 2015 and 2025. The primary objective was to critically assess the relationship between micronutrient status and fertility outcomes in both male and female populations. Studies were selected based on predefined eligibility criteria, which included research on micronutrient supplementation or deficiency, reproductive outcomes, and evidence from randomized controlled trials (RCTs), cohort studies, and meta-analyses. Conclusions Recent research highlights the synergistic effects of these elements, showing that deficiencies or imbalances can exacerbate fertility issues. Optimizing micronutrient levels is becoming an important strategy in fertility management, with potential benefits for both natural conception and assisted reproductive technologies (ART).